Coated and laminated textiles - Fung, Walter (CRC Press ; Woodhead Pub., 2002)
Coating and laminating offer methods of improving and modifying the physical properties and appearance of fabrics and scope for the development of entirely new products by combining the benefits of fabrics, polymers and films. This detailed book covers all aspects of coating and lamination within the textile industry, including compound ingredients, how to set and adhere to strictly controlled processing conditions, the accurate control of production variables, the safe handling of toxic materials and the ongoing research into future products which will facilitate recycling and disposal. It provides particularly useful insight into the challenges and opportunities that these new treatments offer, and is essential reading for technologists, chemists and production engineers working in this exciting field.
Keywords: Coated fabrics.; Laminated fabrics.; elektronické knihy; electronic books